Adlerian Psychology, Interpersonal Relationships, Counseling, Courage, Socratic Dialogue. - Fatmanur Parlak; Mozharul Islam (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This review critically analyzes James Scott's book, Domination and the Arts of Resistance. Scott's account explores the mysteries of unequal power relations in society and the reflection of human behavior in the intellectual world. The book examines the reflections of people's positions on their actions in social life. In addition, by producing new concepts such as public and hidden transcripts, the author contributes to the process of social interpretation. Based on these concepts, Scott tries to analyze why people behave differently in different environments and examine these behaviors' motives. In this way, he explains that the emotions that people involuntarily reflect in some extraordinary situations come from these hidden urges. Within the scope of this book review, we analyzed the book based on Scott's strategies for advancing this scholarship and the relationships in our daily lives. We also tried to emphasize the importance of the book reflected in human life and observed in the social sphere.